Rise of empire - Sullivan, Michael J., 1961- (Sullivan, Michael J., 1961- Riyria revelations, 2011)
"The birth of the Nyphron Empire has brought war to Melengar. To save her kingdom, Princess Arista runs a desperate gamble when she defies her brother and hires Royce and Hadrian to perform a dangerous mission behind enemy lines"--Provided by publisher.